Production of environmentally friendly roofing tiles using palm oil as a binder. Issue 3 (18th September 2017) - Nadeem, Humayun; Habib, Noor Zainab; Aun, Ng Choon; Zoorob, Salah Elias; Mustaffa, Zahiraniza; Nadeem, Sumaira
Abstract : Conventional roofing tiles, composed of either clay or concrete, are considered as environmentally unfriendly since a substantial quantity of greenhouse gases is being discharged in their production. In this study, an alternate approach of utilizing vegetable oil is proposed to produce roofing tiles called 'green roofing tiles'. It is believed that extended heat curing may convert vegetable oil into a rigid binder after undergoing a series of complex autocatalytic oxy-polymerization reactions. These green roofing tiles have flexural strength of up to approximately 11·5 MPa and successfully fulfilled the criteria for water absorption and permeability tests that were conducted in accordance with ASTM standards. Additionally, the leachate characteristics of these novel tiles were also investigated, and it was discovered that these novel roofing tiles have negligible leachate. Remarkably, the embodied energy and carbon dioxide requirements of these tiles were found to be 1·96 MJ/kg and 0·38 kg carbon dioxide equivalent, respectively, which are considered relatively low compared to the values for traditional binders. Conserving existing resources to enable sustainable construction is one of the remarkable outcomes of this research.